2014
DOI: 10.1162/jocn_a_00468
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotional Experiences during Navigation Enhance Parahippocampal Activity during Recall of Place Information

Abstract: Abstract■ It is known that the parahippocampal cortex is involved in object-place associations in spatial learning, but it remains unknown whether activity within this region is modulated by affective signals during navigation. Here we used fMRI to measure the neural consequences of emotional experiences on place memory during navigation. A day before scanning, participants undertook an active object location memory task within a virtual house in which each room was associated with a different schedule of task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…Source localization of this effect pointed to a generator in the right PHC7. This finding resonates with the previous observations, namely, that the right PHC contributes to topographical learning in humans22, feedback and emotion-modulated spatial learning24 and memory25, and that these functions depend on the temporal firing of PHC neurons in relation to the phase of the theta rhythm4.Understood in this context, the theta effect reflects a phase-coded signal by PHC for encoding contextual information about reward location in the environment. The present fMRI experiment was intended to provide converging evidence for this proposal.…”
Section: Discussionsupporting
confidence: 90%
“…Source localization of this effect pointed to a generator in the right PHC7. This finding resonates with the previous observations, namely, that the right PHC contributes to topographical learning in humans22, feedback and emotion-modulated spatial learning24 and memory25, and that these functions depend on the temporal firing of PHC neurons in relation to the phase of the theta rhythm4.Understood in this context, the theta effect reflects a phase-coded signal by PHC for encoding contextual information about reward location in the environment. The present fMRI experiment was intended to provide converging evidence for this proposal.…”
Section: Discussionsupporting
confidence: 90%
“…56,57 Further, it has been implicated in the emotional enhancement of memory representations. 58,59 A recent meta-analysis of whole-brain, voxel-based morphometry studies identified maltreatment-related reductions in parahippocampal gyrus volume across multiple studies, 19 a finding corroborated by subsequent research. 18 Moreover, changes in the structure of the medial temporal lobe, including the parahippocampal gyrus, have been observed in both cross-sectional and prospective studies of early adversity.…”
Section: Discussionmentioning
confidence: 79%
“…The ACC is a key node in emotional regulation (Bush, Luu, & Posner, ), where lesions can result in autonomic dysregulation, apathy, and emotional instability (Cardinal, Parkinson, Hall, & Everitt, ; Devinsky, Morrell, & Vogt, ). The PHG is another important site in emotional processing (Frank et al, ), especially in reactions involving negative emotions (Chan, Baumann, Bellgrove, & Mattingley, ). Regarding the SFG and MFG, they are involved in a variety of cognitive functions, such as working memory, motor control, and attentional reorientation (du Boisgueheneuc et al, ; Japee, Holiday, Satyshur, Mukai, & Ungerleider, ; Martino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ACC is a key node in emotional regulation (Bush, Luu, & Posner, 2000), where lesions can result in autonomic dysregulation, apathy, and emotional instability (Cardinal, Parkinson, Hall, & Everitt, 2002;Devinsky, Morrell, & Vogt, 1995). The PHG is another important site in emotional processing (Frank et al, 2014), especially in reactions involving negative emotions (Chan, Baumann, Bellgrove, & Mattingley, 2014).…”
Section: Discussionmentioning
confidence: 99%